2011
DOI: 10.1039/c0gc00790k
|View full text |Cite
|
Sign up to set email alerts
|

Continuous biocatalytic synthesis of (R)-2-octanol with integrated product separation

Abstract: The continuous biocatalytic synthesis of (R)-2-octanol carried out in an enzyme membrane reactor showed an excellent process stability of the biocatalysts, resulting in a turnover number of 15 million for the applied alcohol dehydrogenase. Utilisation of the ionic liquid AMMOENGTM 101 as a feasible cosolvent increased substrate concentration, and improved space time yields and turnover numbers of the cofactor by factors of 3 and 6, respectively. Moreover, 80% less waste was generated, while producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…To determine enantiomeric excess (ee), samples of the n-heptane phase (250 μL) were mixed with N-MSTFA (50 μL), heated to 80 °C for 30 min and analysed by GC. 13…”
Section: Gas Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…To determine enantiomeric excess (ee), samples of the n-heptane phase (250 μL) were mixed with N-MSTFA (50 μL), heated to 80 °C for 30 min and analysed by GC. 13…”
Section: Gas Chromatographymentioning
confidence: 99%
“…Especially, NR 4 + Cl − -IL were beneficial for the TON of the cofactor as well as for the space-time-yield (STY) and the reaction rate. 12,13 Biocatalysis is generally regarded as safer, greener and more sustainable than conventional chemical catalysis. 14 This is often credited with the fact that water is used as a solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Improved storage stabilities and improved enzyme activities were found in the most promising, ammonium-based, AMMOENG TM 101 IL [32]. Later, the same group [33] proved the feasibility of continuous production using the previously recommended IL, combined with product separation using a membrane bioreactor (the so-called process integration). Hussain and co-workers [34] showed that the use of 10%…”
Section: Oxidoreductasesmentioning
confidence: 95%
“…Using commercially available enzyme membrane reactor, (R)-2-octanol could be continuously synthesized by co-immobilized LbADH and GDH, and produced a fairly high STY of 454 g/(L•d). Additionally, product separation and cofactor recycling were achieved by supercritical carbon dioxide (scCO2) extraction [41] (Table 2).…”
Section: Comparison Of Properties Of D101 and Xda-1mentioning
confidence: 99%